Modular Halogenation, α‐Hydroxylation, and Acylation by a Remarkably Versatile Polyketide Synthase. (26th January 2022) - Hemmerling, Franziska; Meoded, Roy A.; Fraley, Amy E.; Minas, Hannah A.; Dieterich, Cora L.; Rust, Michael; Ueoka, Reiko; Jensen, Katja; Helfrich, Eric J. N.; Bergande, Cedric; Biedermann, Maurice; Magnus, Nancy; et al.
Abstract: Bacterial multimodular polyketide synthases (PKSs) are large enzymatic assembly lines that synthesize many bioactive natural products of therapeutic relevance. While PKS catalysis is mostly based on fatty acid biosynthetic principles, polyketides can be further diversified by post‐PKS enzymes. Here, we characterized a remarkably versatile trans ‐acyltransferase ( trans ‐AT) PKS from Serratia that builds structurally complex macrolides via more than ten functionally distinct PKS modules. In the oocydin PKS, we identified a new oxygenation module that α‐hydroxylates polyketide intermediates, a halogenating module catalyzing backbone γ‐chlorination, and modular O ‐acetylation by a thioesterase‐like domain. These results from a single biosynthetic assembly line highlight the expansive biochemical repertoire of trans ‐AT PKSs and provide diverse modular tools for engineered biosynthesis from a close relative of E. coli . Abstract : Oocydin‐type complex polyketides feature a wide array of structural moieties, resembling the versatility of a Swiss army knife. These include a vinyl chloride, vicinal bis‐oxygens, an O ‐acetylation, and other features. Here it is shown that a functionally greatly expanded polyketide synthase with numerous non‐canonical features assembles these compounds entirely in a modular fashion.